2001
DOI: 10.1128/aac.45.12.3279-3286.2001
|View full text |Cite
|
Sign up to set email alerts
|

Binding Properties of a Peptide Derived from β-Lactamase Inhibitory Protein

Abstract: To overcome the antibiotic resistance mechanism mediated by ␤-lactamases, small-molecule ␤-lactamase inhibitors, such as clavulanic acid, have been used. This approach, however, has applied selective pressure for mutations that result in ␤-lactamases no longer sensitive to ␤-lactamase inhibitors. On the basis of the structure of ␤-lactamase inhibitor protein (BLIP), novel peptide inhibitors of ␤-lactamase have been constructed. BLIP is a 165-amino-acid protein that is a potent inhibitor of TEM-1 ␤-lactamase (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…This finding is promising for inhibitor development and reinforces the results of previous efforts to develop peptide inhibitors. Peptides corresponding to residues 46 -51 of BLIP (the Asp-49 binding loop) were shown to bind TEM-1 and SHV-1 with affinities of 488 and 420 M, respectively (37). Random fragmentation and phage display of BLIP identified a peptide consisting of residues 30 -49 of BLIP that inhibits TEM-1 with 446 M affinity, and a combination of phage display and peptide arrays identified a 136 M inhibitor that has 50% sequence identity to BLIP residues 46 -51 (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is promising for inhibitor development and reinforces the results of previous efforts to develop peptide inhibitors. Peptides corresponding to residues 46 -51 of BLIP (the Asp-49 binding loop) were shown to bind TEM-1 and SHV-1 with affinities of 488 and 420 M, respectively (37). Random fragmentation and phage display of BLIP identified a peptide consisting of residues 30 -49 of BLIP that inhibits TEM-1 with 446 M affinity, and a combination of phage display and peptide arrays identified a 136 M inhibitor that has 50% sequence identity to BLIP residues 46 -51 (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen different oligonucleotide primer pairs were used to replace the wildtype asparagine codon with that for the alternative amino acids. The PCR product was ligated into the pTP123-IMP-1 plasmid and electroporated into E. coli XL1-Blue cells (Stratagene) (38). The colonies were selected on LB agar supplemented with 12.5 g/ml chloramphenicol (6).…”
Section: Methodsmentioning
confidence: 99%
“…Alanine-scanning analysis has revealed that: 1) there are two hotspots on the interacting surface of BLIP, and 2) one mutation (Y50A) actually increases binding affinity for TEM-1 ␤-lactamase by 50-fold (8). Several weak binding peptide inhibitors for TEM-1 have been generated, among which two are the TEM-1-contacting fragments of BLIP (19,20). The contacts of these peptides potentially can be strengthened to create tight binding inhibitors with appropriate enhancement of binding forces.…”
mentioning
confidence: 99%